2009
DOI: 10.1007/s11033-009-9561-z
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide induces the apoptosis in vascular smooth muscle cells via increasing intracellular calcium and ROS formation

Abstract: The present study was designed to investigate whether arsenic trioxide induced the apoptosis in rat mesenteric arterial smooth muscle cells (SMCs), which provides new insights into mechanisms of arsenic-related vascular diseases. Here, we found that arsenic trioxide significantly decreased the viability of SMCs in a dose-dependent manner. In addition, higher level of arsenic trioxide directly caused cellular necrosis. The Hoechst and AO/EB staining demonstrated that apoptotic morphological change was presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…It has been shown that lower concentrations of inorganic arsenic (0.02-0.5 lM) inhibit the myoblast differentiation (Steffens et al 2011;Yen et al 2010). Li et al (2010) reported that higher concentrations of As 2 O 3 (4-32 lM) obviously reduced smooth muscle cell viability in a concentration-dependent manner ). As 2 O 3 (3-10 lM) could also induce apoptosis in cultured bone marrow mesenchymal stem cells Yadav et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that lower concentrations of inorganic arsenic (0.02-0.5 lM) inhibit the myoblast differentiation (Steffens et al 2011;Yen et al 2010). Li et al (2010) reported that higher concentrations of As 2 O 3 (4-32 lM) obviously reduced smooth muscle cell viability in a concentration-dependent manner ). As 2 O 3 (3-10 lM) could also induce apoptosis in cultured bone marrow mesenchymal stem cells Yadav et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that low dose of inorganic arsenic is capable of inhibiting myoblast differentiation (Steffens et al 2011). Arsenic trioxide is known to be used to treat acute promyelocytic leukemia and can induce apoptosis in various cancer and normal cell lines Florea et al 2007;Li et al 2010;Lu et al 2011;Tang et al 2009). Intracellular reactive oxygen species (ROS) mediates multiple cellular responses, including protein kinase activation (Torres and Forman 2003), cell cycle progression (Boonstra and Post 2004), cell differentiation (Yen et al 2010), and apoptotic cell death (Orrenius et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We found that oridonin, a diterpenoid isolated from traditional Chinese medicine Rabdosia rubescens, in combination with As 2 O 3 dramatically enhanced anti-tumor efficacy on human hepatoma cells in vitro and in vivo and this synergistic pro-apoptotic effect resulted from ROS mediated mitochondrial dysfunction and pro-survival signal inhibition. It is known that ROS is a critical mediator for As 2 O 3 induced apoptotic cell death (33), but treatment of Bel7402 cells with a relative low concentration of As 2 O 3 (8 µM) induced no detectable ROS production. Cancer cells seem to have higher level of endogenous oxidative stress compared with normal cells, and the upregulation of antioxidant capacity in adaptation to intrinsic oxidative stress can confer drug resistance (34).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, As decreases in vitro vascular relaxation capability, both endothelium-dependent and endothelium-independent, directly acting on the smooth muscle cells (Lee et al 2003), while it potentiates response to vasoconstrictors through myosin light chain phosphorylation and Ca ++ sensitization/inflow (Lee et al 2005;Li et al 2010;Lim et al 2011). Interaction with arachidonic acid biotransformation, influencing vasoconstriction and relaxation, may be another mechanism (Bunderson et al 2004).…”
Section: Other Mechanisms Of CV Damagementioning
confidence: 99%